Assessment of health status of traffic constables: An occupationally exposed group in Pakistan: Health of traffic constables (Journal of Fatima Jinnah Medical University, 2020)
Background: Traffic constables are exposed to various occupational health hazards worldwide. This study is planned to assess occupational health hazards in traffic constables in Punjab, Pakistan.Subjects and Methods: A descriptive cross-sectional study was conducted in different cities of Punjab including Lahore, Gujranwala, Bahawalpur, Bahawalnagar, Sialkot and Islamabad from March till August 2018. A sample of 384 traffic personals were selected by using non-probability convenient sampling technique. Retired traffic constables and those with work experience less than a year were excluded. A pretested questionnaire was used to conduct the interviews after taking informed consent. Data was collected and analyzed using SPSS version 22 and presented in frequency tables and charts.Results: Maximum number of constables belonged to 31-40 years of age group. Among them 98.7% were male, 25% were having education level above graduation. Results of physical health hazards showed that 53% of warden were smoker, 16.14% were known diabetics and 19.53% were found to be hypertensive. Other physical ailments included respiratory problems (23.4%), hearing impairment or loss (15.88%) and various eye ailments (13.28%). Additionally, 9.1% of participants had evidence of lead poisoning, 33.84% complaints of tightness in muscles and 13.72% of headache, whereas 35.7% had met an accident in the last year. Prevalence of stress and anxiety were 30% and 33.33%. Regarding social health issues 36.7% reported that they were unable to give family time and 42.48% felt lack of independence due to their occupation. Job satisfaction was reported by 50%.Conclusion: The traffic constables in Punjab suffer from a large number of physical, mental and social health issues. Their perception about their occupational health hazards is low and needs improvement through imparting health education.
Keywords: Traffic constables; occupational health hazards; mental health; social health